Single‐cell RNA sequencing reveals developmental heterogeneity among early lymphoid progenitors. (13th October 2017) - Alberti‐Servera, Llucia; von Muenchow, Lilly; Tsapogas, Panagiotis; Capoferri, Giuseppina; Eschbach, Katja; Beisel, Christian; Ceredig, Rhodri; Ivanek, Robert; Rolink, Antonius
Abstract: Single‐cell RNA sequencing is a powerful technology for assessing heterogeneity within defined cell populations. Here, we describe the heterogeneity of a B220 + CD117 int CD19 − NK1.1 − uncommitted hematopoietic progenitor having combined lymphoid and myeloid potential. Phenotypic and functional assays revealed four subpopulations within the progenitor with distinct lineage developmental potentials. Among them, the Ly6D + SiglecH − CD11c − fraction was lymphoid‐restricted exhibiting strong B‐cell potential, whereas the Ly6D − SiglecH − CD11c − fraction showed mixed lympho‐myeloid potential. Single‐cell RNA sequencing of these subsets revealed that the latter population comprised a mixture of cells with distinct lymphoid and myeloid transcriptional signatures and identified a subgroup as the potential precursor of Ly6D + SiglecH − CD11c − . Subsequent functional assays confirmed that B220 + CD117 int CD19 − NK1.1 − single cells are, with rare exceptions, not bipotent for lymphoid and myeloid lineages. A B‐cell priming gradient was observed within the Ly6D + SiglecH − CD11c − subset and we propose a herein newly identified subgroup as the direct precursor of the first B‐cell committed stage. Therefore, the apparent multipotency of B220 + CD117 int CD19 − NK1.1 − progenitors results from underlying heterogeneity at the single‐cell level and highlights the validity of single‐cell transcriptomics for resolving cellular heterogeneity and developmental relationships among hematopoietic progenitors. Synopsis: Single‐cell transcriptomic analysis shows that phenotypically indistinguishable multi‐potent lympho‐myeloid hematopoietic progenitors are genotypically heterogeneous and identifies a subgroup as the potential precursor of the first B‐cell committed progenitor. Phenotypic and functional analysis of the multipotent progenitor EPLM reveal four subpopulations with distinct lineage developmental potentials. Single‐cell RNA‐seq reveals that EPLM is a heterogeneous population composed of a mixture of cells with distinct genetic signatures. Single cells with combined lympho‐myeloid genotypic or developmental potential are not observed. One subset shows a B‐cell priming gradient. Abstract : A mouse hematopoietic precursor population with presumed multilineage potential is on the single‐cell level composed of cells with distinct lymphoid and myeloid genetic signatures.